Occupational health and physiological profile of sericulture industry workers with respect to Workplace environment - RESHMA A. SANADI,; A.D. JADHAV, (International Journal of Pharma and Bio Sciences, 2016)
The sericulture industry is a labor-intensive agro based industry in India. The workforce is exposed to various occupational factors at the workplace and hence, they are susceptible to various occupational hazards. The present study was undertaken to correlate the physiological response of sericulture industry workers and their workplace environment. Demographic data of workers were collected by standard questionnaire. Data was analyzed by using standard statistical procedures. In the present study it was observed that, the workers were not aware of health and safety issues due to the majority of workers are illiterate. The workplace environment is characterized by the presence of various chemicals, noise, heat, spiteful smell and lime dust/biological dust in various activities of sericulture industry. Working environment is affecting on workers health and they were exposed to various types of health risk factors. Physiological profile of workers shows variation in body temperature, pulse rate, BP, Hand grip strength and Peak expiratory flow rate (PEFR) values.